2000
DOI: 10.1046/j.1432-1327.2000.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of antimony tartrate with the tripeptide glutathione

Abstract: The tripeptide glutathione (g-l-Glu-l-Cys-Gly, GSH) is thought to play an important role in the biological processing of antimony drugs. We have studied the complexation of the antileishmanial drug potassium antimony(III) tartrate to GSH in both aqueous solution and intact red blood cells by NMR spectroscopy and electrospray ionization mass spectrometry. The deprotonated thiol group of the cysteine residue is shown to be the only binding site for Sb (III), and a complex with the stoichiometry [Sb(GS) 3 ] is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 29 publications
3
78
0
Order By: Relevance
“…Although a significant increase in the DCF fluorescence by the treatment of Sb was not observed, the data show a dose-dependent correlation. The increasing trend in the generation of ROS in the presence of a high concentration of Sb or As exposure can be explained by studies of several cell lines, which have shown the formation of oxidative stress at high concentrations of As(III) (Alarifi et al, 2013;Selvaraj et al, 2013) and the depletion of glutathione in complex with Sb(III) or As(III) (Burford et al, 2005) (Sun et al, 2000;Kobayashi et al, 2005), resulting in the disturbance of the intracellular redox balance.…”
Section: Mitochondrial Activity In the Presence Of Sb(iii) And Sb(v) mentioning
confidence: 99%
See 2 more Smart Citations
“…Although a significant increase in the DCF fluorescence by the treatment of Sb was not observed, the data show a dose-dependent correlation. The increasing trend in the generation of ROS in the presence of a high concentration of Sb or As exposure can be explained by studies of several cell lines, which have shown the formation of oxidative stress at high concentrations of As(III) (Alarifi et al, 2013;Selvaraj et al, 2013) and the depletion of glutathione in complex with Sb(III) or As(III) (Burford et al, 2005) (Sun et al, 2000;Kobayashi et al, 2005), resulting in the disturbance of the intracellular redox balance.…”
Section: Mitochondrial Activity In the Presence Of Sb(iii) And Sb(v) mentioning
confidence: 99%
“…Protein aggregates in yeast, even those of chaperone proteins, were suggested to the interact using the sulfhydryl groups of Cys (Jacobson et al, 2012). In the case of Sb, no study clearly addresses that its protein aggregates in living cells exist, although some studies for the interaction of Sb with biomolecules, such as glutathione, adenine and guanine nucleosides, obtained by 13 C and 1 H NMR, ESI-MS and circular dichroism (Burford et al, 2005;Demicheli et al, 2002;Sun et al, 2000) have been reported. Although the hitherto study mentioned that the toxicological mechanisms of Sb may be quite similar to those of As because of the physicochemical similarities of Sb to As (Beyersmann and Hartwig, 2008), the results obtained in this study show some toxicological differences between Sb and As.…”
Section: Mitochondrial Activity In the Presence Of Sb(iii) And Sb(v) mentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism of efflux remains uncertain, but previous studies on plasma membrane vesicles have shown that Leishmania cell lines actively extrude 73 As (as arsenite) in the presence of ATP and either glutathione or trypanothione at equal rates (19). Based on the fact that Sb III inhibits this activity (18), coupled with the fact that Sb III forms a complex with either glutathione (38) or trypanothione (39), it has been postulated that Sb III is effluxed in a similar fashion. Although this is an attractive hypothesis, direct demonstration of cotransport of antimony and thiol is lacking.…”
Section: Effects Of Pentavalent Antimony On the Thiol Metabolism Of Lmentioning
confidence: 99%
“…Spontaneous formation of Sb(III) complexed with either glutathione, trypanothione or both has been demonstrated by proton nuclear magnetic resonance spectroscopy (140,162) and by mass spectrometry (107). Since glutathione S-transferase (GST) is elevated in mammalian cells selected for resistance to arsenite (97), it has been proposed that formation of the metalloid-thiol pump substrates in Leishmania spp.…”
Section: Antimonialsmentioning
confidence: 99%